Exploration Of Islamic Religious Education Program At Ma`Had Al Jamia`Ah An Effort To Include Multicultural Values In The Millennial Generation - Indrawari, Karliana; Madi, Madi Apriadi; Lia Pitrianingsih; Rizki Yunita Putri (El-Ghiroh : Jurnal Studi Keislaman, 2025)
The purpose of this study is to find out the multicultural values instilled in the millennial generation in Ma'had Aljamiah, this research is motivated by the degradation of national morality values that are really concerning and multicultural problems that cause conflict prone to changes caused by radical elements in the millennial generation. This type of research is qualitative research research with a descriptive approach, the data collection techniques used are observation, interviews, and documentation. The results of this study show that the strengthening of multicultural values in Mahad Al Jamiah to instill the character of students has been realized through a moral knowing approach. Every night Monday to Thursday, students learn to recite, Friday is filled with yasinan, and the mauizotul hasanah program is implemented. Ustadz and ustadzah alternately delivered material on Islamic creeds, morals, morals, and laws. Saturday night is filled with muhadoroh activities for self-development. Strengthening through moral feeling is applied by instilling a sense of empathy and mutual help among students. Strengthening through moral action is reflected in the obligation of congregational prayer and discipline in Mahad Al Jamiah IAIN Curup. Factors supporting the strengthening of multicultural values of the millennial generation in Mahad Al Jamiah IAIN Curup are influenced by the students themselves, the support of ustadz/ustadzah, seniors, ma'had administrators, dorm friends, and various activities. However, inhibiting factors can arise from the students themselves.